Identification of ANXA2 (annexin A2) as a specific bleomycin target to induce pulmonary fibrosis by impeding TFEB-mediated autophagic flux. Issue 2 (1st February 2018) - Wang, Kui; Zhang, Tao; Lei, Yunlong; Li, Xuefeng; Jiang, Jingwen; Lan, Jiang; Liu, Yuan; Chen, Haining; Gao, Wei; Xie, Na; Chen, Qiang; Zhu, Xiaofeng; et al.
ABSTRACT: Bleomycin is a clinically potent anticancer drug used for the treatment of germ-cell tumors, lymphomas and squamous-cell carcinomas. Unfortunately, the therapeutic efficacy of bleomycin is severely hampered by the development of pulmonary fibrosis. However, the mechanisms underlying bleomycin-induced pulmonary fibrosis, particularly the molecular target of bleomycin, remains unknown. Here, using a chemical proteomics approach, we identify ANXA2 (annexin A2) as a direct binding target of bleomycin. The interaction of bleomycin with ANXA2 was corroborated both in vitro and in vivo. Genetic depletion of anxa2 in mice mitigates bleomycin-induced pulmonary fibrosis. We further demonstrate that Glu139 (E139) of ANXA2 is required for bleomycin binding in lung epithelial cells. A CRISPR-Cas9-engineered ANXA2 E139A mutation in lung epithelial cells ablates bleomycin binding and activates TFEB (transcription factor EB), a master regulator of macroautophagy/autophagy, resulting in substantial acceleration of autophagic flux. Pharmacological activation of TFEB elevates bleomycin-initiated autophagic flux, inhibits apoptosis and proliferation of epithelial cells, and ameliorates pulmonary fibrosis in bleomycin-treated mice. Notably, we observe lowered TFEB and LC3B levels in human pulmonary fibrosis tissues compared to normal controls, suggesting a critical role of TFEB-mediated autophagy in pulmonary fibrosis. Collectively, our data demonstrate that ANXA2 is a specific bleomycin target, and bleomycin binding with ANXA2 impedes TFEB-induced autophagic flux, leading to induction of pulmonary fibrosis. Our findings provide insight into the mechanisms of bleomycin-induced fibrosis and may facilitate development of optimized bleomycin therapeutics devoid of lung toxicity.